1997
DOI: 10.1159/000134726
|View full text |Cite
|
Sign up to set email alerts
|

A novel allelic variant of the human serotonin transporter gene regulatory polymorphism

Abstract: Allelic variation of the human serotonin transporter gene (SLC6A4) has recently been shown to modulate anxiety-related traits. A tandemly repeated sequence in close proximity to the promoter was found to be represented by a long (L) and short (S) variant, differentially modulating gene expression in vitro. Specifically, allele S, generated by a deletion of 44 bp involving repeats VI to VIII, reduced transcriptional efficiency, gene expression, and 5-hydroxytryptamine uptake and was associated with increased ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 17 publications
2
41
0
Order By: Relevance
“…The frequencies of the l and s alleles in this sample are consistent with the population (eg Delbruck et al, 1997;Gelernter et al, 1999). For example, in Caucasians, the frequencies for ll is about 3575% and sl/ss is about 6575% (l is about 60% and s about 40%).…”
Section: Resultssupporting
confidence: 80%
“…The frequencies of the l and s alleles in this sample are consistent with the population (eg Delbruck et al, 1997;Gelernter et al, 1999). For example, in Caucasians, the frequencies for ll is about 3575% and sl/ss is about 6575% (l is about 60% and s about 40%).…”
Section: Resultssupporting
confidence: 80%
“…97 In addition, up to 10 new alleles were discovered in the 5-HTT promoter polymorphism, some of which were only present in Japanese samples. [118][119][120][121][122] Also the allele frequency distribution of the DRD4 48-bp VNTR differs widely across ethnic groups. 123 As is evident from studies in affected populations, personality can be greatly affected by the disease status.…”
Section: Replicabilitymentioning
confidence: 99%
“…A polymorphism within the 5-htt 5' upstream region (5-HTTLPR) has been reported, the majority of which is composed of either 14 (S) or 16 (L) repetitive elements. In humans, although infrequent, 18 and 20 repetitive elements (XL) are also present (18)(19)(20)(21). An in vitro transcriptional assay has indicated that the activity of the human 5-htt promoter is regulated by these polymorphic repetitive elements, resulting in differences in the efficacy of 5-HTT reuptake among the allelic variants (22).…”
Section: Introductionmentioning
confidence: 99%